2008
DOI: 10.1111/j.1464-410x.2008.07563.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaporization of prostates of ≥80 mL using a potassium‐titanyl‐phosphate laser: midterm‐results and comparison with prostates of <80 mL

Abstract: OBJECTIVETo compare the safety and outcome of potassium‐titanyl‐phosphate (KTP) GreenlightTM (Laserscope, AMS, Minnetonka, MN, USA) vaporization for treating benign prostatic hyperplasia (BPH) in prostates of ≥80 vs <80 mL.PATIENTS AND METHODSIn all, 204 consecutive patients were enrolled into this prospective study; 31 were excluded from analysis for various reasons, thus 173 (median age 66.8 years; 39 with prostates of ≥80 mL) were evaluated for maximum urinary flow rate (Qmax), postvoid residual urine (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 18 publications
(30 reference statements)
2
28
1
Order By: Relevance
“…[12,13] The role of KTP laser vaporization is still controversial in cases of large-volume prostates. In their study, with a median follow-up of 11.7 months, Pfitzenmaier et al [14] found similar functional outcomes in terms of improvements in QMax, IPSS, and QOL scores, but a serious trend toward a higher reoperation rate, 23.1% vs. 10.4%, in larger prostates (>80 mL) compared with that in smaller glands (<80 mL). In our study, only 4 (13.3%) patients had a prostate volume greater than 80 mL, but we did not see any difference in efficacy or reoperation rate.…”
Section: Discussionmentioning
confidence: 75%
“…[12,13] The role of KTP laser vaporization is still controversial in cases of large-volume prostates. In their study, with a median follow-up of 11.7 months, Pfitzenmaier et al [14] found similar functional outcomes in terms of improvements in QMax, IPSS, and QOL scores, but a serious trend toward a higher reoperation rate, 23.1% vs. 10.4%, in larger prostates (>80 mL) compared with that in smaller glands (<80 mL). In our study, only 4 (13.3%) patients had a prostate volume greater than 80 mL, but we did not see any difference in efficacy or reoperation rate.…”
Section: Discussionmentioning
confidence: 75%
“…Table 5 shows reoperation rates for recurrent obstruction in different contemporary series. 4,8,9,13,14,16,18,20,21 The reoperation rate for recurrent or residual adenoma was 2% to 13% with more association with larger glands, early training and intraoperative bleeding. In our series the reoperation rate for recurrent or residual adenoma was 2.1%, commonly in glands greater than 50 ml.…”
Section: Discussionmentioning
confidence: 98%
“…1 At 80 W PVP with the KTP laser could become laborious when performed on large prostates, and lead to incomplete tissue removal. [2][3][4] Thus, the more powerful 120 W, 532 nm, quasicontinuous wave GreenLight HPS laser generator was introduced. 5, 6 The HPS uses an LBO crystal and delivers the same green 532 nm wavelength through the same 70-degree deflecting, side firing, silica fiber delivery device but by an 88% more collimated beam and smaller spot size, resulting in much higher irradiance or power density in W/cm 2 than its predecessor with a beam divergence of 8 vs 15 degrees.…”
mentioning
confidence: 99%
“…Pfitzenmaier et al [22] compared the safety and outcome of KTP for treating BPH in prostates of greater than or equal to 80 mL versus less than 80 mL. Out of 173 patients included in the analysis, 56 were on OA.…”
Section: Potassium Titanyl Phosphate Laser Photovaporizationmentioning
confidence: 99%